Society in an age of plague - Clark, Linda, 1946-; Rawcliffe, Carole, 1946- (Fifteenth century., 2013)
Described as 'a golden age of pathogens', the long fifteenth century was notable for a series of international, national and regional epidemics that had a profound effect upon the fabric of society. The impact of pestilence upon the literary, religious, social and political life of men, women and children throughout Europe and beyond continues to excite lively debate among historians, as the ten papers presented in this volume confirm. They deal with the response of urban communities in England, France and Italy to matters of public health, governance and welfare, as well as addressing the r ...